Non-acidic method for isolation of microcrystalline cellulose from oil palm empty fruit bunch fiber - Samat, Noorasikin; Ghazali, Nurul Najihah; Ahmad, Zuraida; Ali, Fathilah (International Journal of Engineering and Technology(UAE), 2018)
In this study, the microcrystalline cellulose (MCC) was extracted via a non-acidic method from the oil palm empty fruit bunch (EFB) cellulose. The extraction was conducted through Ammonium Persulfate (APS) oxidation treatment, which was followed by the ball milling process. The effects of varied temperature levels from APS oxidation treatment (60, 80 and 90oC) and different milling time (1, 4 hours) were investigated. APS oxidation treatment at 90oC was found to produce the most optimum results. The size of the MCC was less than 20μm and had demonstrated the highest degree of crystallinity index and thermal stability. The high crystallinity index is associated with the removal of non-cellulosic components as seen from FTIR analysis, where a decrease was observed in the characteristic peak intensity of 1735 and 1510 cm-1. The milling time had also affected the formation of MCC. Although a relatively longer milling time had produced smaller MCC with narrow size distribution, it had, however, given rise to a slight adverse effect on the crystallinity index and thermal stability.